Children’s Experiences of Time when a Parent Travels for Work - Zvonkovic, Anisa (J Marriage Fam, 2016)
This qualitative study focuses on different ways time is experienced by children in families who face time challenges due to a family member’s job that required work travel. Data are from a family-level study that includes interviews of all family members over the age of 7. Using grounded theory methodology, this study illustrates ways in which job demands and family processes interact. Analysis centers on the 75 children’s perspectives from 43 families. Holding together assessments of having enough time while wanting more time with their parents, children express emotion, generally unrecognized by parents, around the topic of family time. Children’s experience of time with parents is rushed or calm, depending on the activities done in time and the gender of the parent with whom they spend time. Findings are interpreted through a feminist social constructionist lens.